Policy Implementation in Higher Education: The Dynamics of a Fall Break - Pilato, Kelly A.; Law, Madelyn P.; Moore, Shannon A.; Hay, John A.; Narushima, Miya (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2022)
A case study using mixed methods that critically appraises the implementation of a mental health policy in higher education in the absence of evidence to inform the policy using an exemplar case from one mid-sized post-secondary institution was the motivation for this research. Explanation building was used to iteratively analyse data on rival explanations of the implementation of the fall break policy. Analyses from the surveys revealed that overall, only 36.9 per cent of students perceived an increase in workload before the break and only 29.6 per cent of students perceived an increase in workload after the break. However, the focus groups and professor interviews revealed that the timing of the fall break had an impact on how students and professors experienced the break and their perceptions on its impact on student mental health. If baseline data regarding the implementation of the fall break would have been collected prior to its implementation, we could have possibly avoided the implementation issues that arose. While this research provides an exemplar case of a fall break policy at one post-secondary institution, the policy learning is universal.